Facile synthesis of a multifunctional ternary SnO2/MWCNTs/PANI nanocomposite: Detailed analysis of dielectric, electrochemical, and water splitting applications. (10th February 2023) - Khan, Muhammad Zarrar; Gul, Iftikhar Hussain; Baig, Mutawara Mahmood; Akram, Muhammad Aftab
Abstract: Herein, a SnO2 /MWCNTs/PANI nanocomposite was synthesized using a wet chemical approach which acts as a multifunctional electrode for supercapacitor and hydrogen evolution reaction. The dielectric properties were studied using the Maxwell-Wagner model of space charge polarization. The increasing dielectric constant indicated the suitability of synthesized NPs for telecommunication, electronics, and other high-frequency applications. The dependence of impedance and dielectric behavior on grains and grain boundaries was further investigated via impedance spectroscopy and complex electric modulus. Based on a 6 M KOH aqueous electrolyte, the SnO2 /MWCNTs/PANI as an electrode material for supercapacitors displays a capacity of 211 C g −1 at 1 A g −1 and exhibits excellent cycling stability with a capacitance retention ratio of 98% after 5000 cycles at a current density of 2 A g −1 . For hydrogen evolution reaction in 0.5 M KOH, SnO2 /MWCNTs/PANI electrode achieves a benchmark of 10 mA cm −2 at overpotentials of 524 mV. The results reveal that the SnO2 /MWCNTs/PANI nanocomposite act as multifunctional material that can be used for both energy storage and conversion. Graphical abstract: Image, graphical abstract